HUBUNGAN ANTARA KECENDERUNGAN PERILAKU MENGAKSES SITUS PORNO DAN RELIGIUSITAS PADA REMAJA - Diah Viska Rahmawati; M Noor Rochman Hadjam; Tina Afiatin (Jurnal Psikologi, 2002)
The main purpose of this research is to see the correlations between tendency to access porn site and religiousity in adolescent. Total research subject is 83 users of Cupido and Intersat Nusantara Cyber Cafe. Research variables are measured by scale method, those are Tendency to Access Porn Site Scale which consists 48 items composed by researcher herself and Religiousity Scale by Turmudhi (1991). Religiousity Scale consists of 2 part, the first part contains 68 items with 12 pairs identical item for consistency test (not used for further analysis) and the second part contains 27 items specially for intellectual dimension from religiousity. The Product Moment analysis results that there’s significant negative correlation between tendency to access porn site and religiousity (rxy = -0.208; p = 0.029, p′0.05). Which means, the more adolescent religious, the less tendency to access porn site and viceversa, while religiousity gives effective contribution to tendency to access porn site for about 4.3%. The t– test shows that the difference tendency to access porn site between male and female adolescent is quite significant ( XL = 109.04 ∃ XP = 85.97, t = 5.221; p =0.000, p′0.01). It means, male adolescent has higher tendency to access porn site than female adolescent. Keywords: access porn site, religiousity, adolescent.